2009
DOI: 10.1007/978-3-642-03816-7_34
|View full text |Cite
|
Sign up to set email alerts
|

Time-Bounded Kolmogorov Complexity and Solovay Functions

Abstract: Abstract.A Solovay function is a computable upper bound g for prefixfree Kolmogorov complexity K that is nontrivial in the sense that g agrees with K, up to some additive constant, on infinitely many places n. We obtain natural examples of Solovay functions by showing that for some constant c0 and all computable functions t such that c0n ≤ t(n), the time-bounded version K t of K is a Solovay function.By unifying results of Bienvenu and Downey and of Miller, we show that a right-computable upper bound g of K is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…The characterization of weak Solovay functions in Theorem 2.2 holds also when relativized to any oracle by virtually the same proof. In fact, Hölzl, Kräling and Merkle [17] demonstrated the relativized version, as a joint generalization of, first, the already mentioned corresponding characterization of Solovay functions by Bienvenu and Downey [5], and, second, a remarkable characterization of the sequences that are weakly low for K by Miller [29]. For the sake of completeness, we shortly review the latter result, which now becomes a special case of Theorem 2.2.…”
Section: A Criterion For Being a Solovay Functionmentioning
confidence: 76%
See 2 more Smart Citations
“…The characterization of weak Solovay functions in Theorem 2.2 holds also when relativized to any oracle by virtually the same proof. In fact, Hölzl, Kräling and Merkle [17] demonstrated the relativized version, as a joint generalization of, first, the already mentioned corresponding characterization of Solovay functions by Bienvenu and Downey [5], and, second, a remarkable characterization of the sequences that are weakly low for K by Miller [29]. For the sake of completeness, we shortly review the latter result, which now becomes a special case of Theorem 2.2.…”
Section: A Criterion For Being a Solovay Functionmentioning
confidence: 76%
“…This characterization extends trivially to the special case of Solovay functions in the sense that among all computable functions exactly the Solovay functions possess the property under consideration. Note that in case of the first property the latter characterization was shown in a conference article by the first two authors of this paper [5], whereas the corresponding characterization of weak Solovay functions was subsequently demonstrated by Hölzl, Kräling and Merkle [17], see Section 2.2 for further details.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…(An observation of Hölzl, Kräling, and Merkle [40].) Building on earlier work of Gács, and of Miller and Yu, recently Merkle, Miller and Nies have proven that a set A is 1-random iff C(A n) ≥ n − g(n) − O(1) for any Solovay function g. In fact by themselves, Solovay functions characterize 1-randomness.…”
Section: Definition 4 (Bienvenu and Merkle [11]) A Computable Functimentioning
confidence: 90%
“…Note that log n is an upper bound of C(n). Hölzl, Kräling and Merkle [HKM09] observed that, in fact, for every c.e. set A there are infinitely many n such that C(A ↾ n ) is bounded by C(n) (plus an additive constant); this also holds for prefix-free complexity.…”
Section: Measuring the Complexity Of A Computably Enumerable Setmentioning
confidence: 98%